Reverse Osmosis Seawater Desalination Volume 2 c y Heinz Ludwig. - Ludwig, Heinz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Seawater reverse osmosis (SWRO) is the dominant desalination process worldwide for obtaining fresh water from the sea. The subject matter and scope of this book is the conceptual and advanced planning, design and engineering of plants of this desalination process together with the associated facilities for seawater pretreatment, post-treatment of the product water, wastewater treatment, seawater extraction and plant discharge. Volume 2 of this book covers Design of the pretreatment and post-treatment processes as well as of the sea water extraction and outfall systems of SWRO - explanation of the basic principles and design approaches and their application in the practical dimensioning of the units Description of the wastewater treatment facilities of an SWRO and their design Liquid and solid residues of SWRO, their amount and environmental aspects and regulations of their discharge and disposal and possibilities of their recovery and reuse Material selection for the SWRO components Description of the control systems of an SWRO and their interaction with manual sampling and analysis for operation control of the plant Determination of specific energy consumption of an SWRO and the influence of design and plant operation on its optimisation Contractual structures and economic aspects of planning and implementation an SWRO, calculation of the capital, operating and water production costs of the plant The book is intended to be used by technicians, engineers, economists and ecologists as a working tool in the planning, design and operation of reverse osmosis desalination plants and by students and teachers as an introduction to this subject, as well as by employees of environmental authorities as an aid in environmental licensing of membrane desalination plants and by interested laypersons for information about this process. Heinz Ludwig gained his professional expertise during more than five decades of business in the fields of seawater desalination technologies, environmental protection and treatment of process water, drinking water and waste water. In seawater desalination he was involved in a multitude of worldwide projects of brackish water and seawater desalination with thermal processes and membrane technologies. .
Pretreatment -- Posttreatment -- Seawater Extraction and Supply, and Concentrate Discharge -- SWRO Effluents and Residues - Composition, Environmental Impacts, Discharge and Disposal Regulations and Treatments Measures -- Materials for SWRO Plants -- SWRO Plant Operation Organization, Monitoring and Instrumentation -- Energy Consumption of an SWRO Plant -- Economics, Life Cycle Cost and Water Production Cost.
Keywords: Environmental engineering; Civil engineering; Production engineering; Marine engineering; Biotechnology; Bioremediation; Environmental Civil Engineering; Process Engineering; Marine Engineering; Environmental Engineering/Biotechnology.; Saline water conversion -- Reverse osmosis process